2015
DOI: 10.1038/cmi.2014.126
|View full text |Cite
|
Sign up to set email alerts
|

The Galectin-9/Tim-3 pathway is involved in the regulation of NK cell function at the maternal–fetal interface in early pregnancy

Abstract: Decidual natural killer (dNK) cells actively participate in the establishment and maintenance of maternal-fetal immune tolerance and act as local guardians against infection. However, how dNK cells maintain the immune balance between tolerance and anti-infection immune responses during pregnancy remains unknown. Here, we demonstrated that the inhibitory molecule T-cell immunoglobulin domain and mucin domain-containing molecule-3 (Tim-3) are expressed on over 60% of dNK cells. Tim-3 1 dNK cells display higher i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
128
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(138 citation statements)
references
References 44 publications
(44 reference statements)
0
128
1
1
Order By: Relevance
“…39,42 Apart from trophoblast invasion and vascular remodeling, dNK cells participate in the process of decidualization and the promotion of F I G U R E 3 There is a negative correlation between CD82 and CD29 on CD56 dim dNK cells. 39,42 Apart from trophoblast invasion and vascular remodeling, dNK cells participate in the process of decidualization and the promotion of F I G U R E 3 There is a negative correlation between CD82 and CD29 on CD56 dim dNK cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…39,42 Apart from trophoblast invasion and vascular remodeling, dNK cells participate in the process of decidualization and the promotion of F I G U R E 3 There is a negative correlation between CD82 and CD29 on CD56 dim dNK cells. 39,42 Apart from trophoblast invasion and vascular remodeling, dNK cells participate in the process of decidualization and the promotion of F I G U R E 3 There is a negative correlation between CD82 and CD29 on CD56 dim dNK cells.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have demonstrated the key role of dNK cells in the establishment and maintenance of maternal immunotolerance to the fetus, such as secreting Th2-type cytokines and affecting the differentiation of regulatory T (Treg) cells. 39,42 Apart from trophoblast invasion and vascular remodeling, dNK cells participate in the process of decidualization and the promotion of F I G U R E 3 There is a negative correlation between CD82 and CD29 on CD56 dim dNK cells. A, CD29 expression on dNK cells from women with normal pregnancies (n = 9) and RSA patients (n = 8) was analyzed by FCM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Other studies have reported trophoblast cells express and secrete LGALS9, and via the LGALS9/HAVCR2 signalling pathway, can induce natural killer (NK) cells to differentiate into decidual-like NK (dNK) cells. 49 These HAVCR2 + dNK cells produce high levels of IL4 and low TNF. Therefore, it is feasible that LGALS9 could be used in the management of preterm birth by increasing HAVCR2 activation to reduce inflammation associated with labour.…”
Section: Studies In Non-gestational Tissues Show Poly(i:c) Regulatesmentioning
confidence: 99%
“…and function [14,25,26]. Previous studies conducted by our research group has reported the 74 expression off galectins in ruminants [27].…”
mentioning
confidence: 99%